Paleopathological Considerations on Malaria Infection in Korea before the 20th Century. (9th May 2018) - Shin, Dong Hoon; Seo, Min; Hong, Jong Ha; Lee, Eunju
Abstract : Malaria, one of the deadliest diseases in human history, still infects many people worldwide. Among the species of the genus Plasmodium, P. vivax is commonly found in temperate-zone countries including South Korea. In this article, we first review the history of malarial infection in Korea by means of studies on Joseon documents and the related scientific data on the evolutionary history of P. vivax in Asia. According to the historical records, malarial infection was not unusual in pre-20th-century Korean society. We also found that certain behaviors of the Joseon people might have affected the host-vector-pathogen relationship, which could explain why malarial infection prevalence was so high in Korea at that time. In our review of genetic studies on P. vivax, we identified substantial geographic differentiation among continents and even between neighboring countries. Based on these, we were able to formulate a strategy for future analysis of ancient Plasmodium strains in Korea.